Understanding the pathways to resilience in university students in a UK-based higher education setting: a socio-ecological approach - Dutta, Snigdha (2021)
Background: The mental health and well-being of university students has been deemed a global concern due to the rising prevalence of poor mental health and psychosocial functioning. The thesis's impetus was drawn from the increased advocacy for resilience promotion in university students by higher education-based policies. A review of resilience literature within the higher education context illuminated several discrepancies in the conceptual and operational enquiry of resilience for this specific population. Specifically, the study of resilience within the higher education setting has primarily been individual-focused which has discounted the risk or protective role of family and social factors. Additionally, a review of the resilience-based interventions for university students indicated the need for a systematic theoretical and empirical delineation of the complex construct.